Income Shocks, Inequality, and Democracy. (20th August 2020) - Kotschy, Rainer; Sunde, Uwe
Abstract: In this paper, motivated by contradictory evidence on the effect of income on democracy, we investigate the hypothesis that it is income shocks – major income fluctuations relative to the trend – rather than marginal year‐on‐year variation in income levels that lead to non‐trivial changes in the quality of political institutions. Empirical results provide support for this hypothesis, and show how income inequality plays a crucial role in the effects of economic shocks on democracy. In particular, negative income shocks reveal a positive effect on democracy in countries with high inequality, and vice versa.